Effects of daily static stretch training over 6 weeks on maximal strength, muscle thickness, contraction properties, and flexibility - Wohlann, Tim; Warneke, Konstantin; Hillebrecht, Martin; Petersmann, Astrid; Ferrauti, Alexander; Schiemann, Stephan (Frontiers in Sports and Active Living, 2023)
Purpose Static stretch training (SST) with long stretching durations seems to be sufficient to increase flexibility, maximum strength (MSt) and muscle thickness (MTh). However, changes of contraction properties and effects on muscle damage remain unclear. Consequently, the objective of the study was to investigate the effects of a 6-week self-performed SST on MSt, MTh, contractile properties, flexibility and acute response of creatine kinase (CK) 3 days after SST. Methods 44 participants were divided into a control (CG, n = 22) and an intervention group (IG, n = 22), who performed a daily SST for 5 minutes for the lower limb muscle group. While isometric MSt was measured in leg press, MTh was examined via sonography, and flexibility by using functional tests. Muscle stiffness and contraction time were measured using tensiomyography on rectus femoris. Additionally, capillary blood samples were taken in pre-test and at the first 3 days after starting SST to measure CK. Results A significant increase was found for MSt (p < 0.001, ƞ² = 0.195) and flexibility in all functional tests (p < 0.001, ƞ² > 0.310). Scheffé post hoc test didn’t show significant differences for MTh between the rectus femoris muscle inter- and intragroup comparisons, nor for muscle stiffness and contraction time (p > 0.05, ƞ² < 0.100). Moreover, CK was not significantly different between IG and CG with p > 0.05, ƞ² = 0.032. Discussion In conclusion, the increase in MSt cannot be exclusively explained by muscular hypertrophy or increased CK-related repair mechanism after acute stretching. Rather, neuronal adaptations have to be considered. Furthermore, daily 5-minute SST over 6 weeks does not seem to be sufficient to change muscle stiffness or contraction time. Increases in flexibility tests could be attributed to a stretch-induced change of muscle-tendon complex.